2016
DOI: 10.2174/1568009616666160216125634
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP Activation of TGF-? Signaling Enables Intercellular Activation of an Epithelial-mesenchymal Transition Program in Cancer

Abstract: Membrane type 1-matrix metalloproteinase (MT1-MMP, MMP-14) is associated with cancer invasion and metastasis leading to poor patient prognosis. MT1-MMP mediates cancer cell invasion via degradation of basement membrane and extracellular matrix, and induction of cell migration. However, MT1-MMP expression in the cancer stroma can drive invasion of carcinoma cells in vivo, suggesting MT1-MMP may also promote cancer invasiveness via paracrinemediated mechanisms. A major step in cancer cell metastasis is thought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…This conclusion is further supported by the identification of ERG + SMA + cells with active SMAD2 signaling pathway within the infarction and by the results obtained in in vitro experiments. Our findings are in line with the role of MT1-MMP as an activator of epithelial to mesenchymal transition (EMT) in other pathophysiological contexts such as development, cancer, and lung fibrosis (Garmon et al, 2018;Nguyen et al, 2016;Xiong et al, 2017). Interestingly, a recent scRNAseq study carried out on healthy and post-infarcted hearts identified a subset of post-MI Mφs with a HIF1α-dependent signature, which specifically upregulated Mmp14 expression (Dick et al, 2019).…”
Section: Mφ-derived Mt1-mmp Induces Endmt After MIsupporting
confidence: 86%
“…This conclusion is further supported by the identification of ERG + SMA + cells with active SMAD2 signaling pathway within the infarction and by the results obtained in in vitro experiments. Our findings are in line with the role of MT1-MMP as an activator of epithelial to mesenchymal transition (EMT) in other pathophysiological contexts such as development, cancer, and lung fibrosis (Garmon et al, 2018;Nguyen et al, 2016;Xiong et al, 2017). Interestingly, a recent scRNAseq study carried out on healthy and post-infarcted hearts identified a subset of post-MI Mφs with a HIF1α-dependent signature, which specifically upregulated Mmp14 expression (Dick et al, 2019).…”
Section: Mφ-derived Mt1-mmp Induces Endmt After MIsupporting
confidence: 86%
“…ECM proteins stimulate integrin receptors on the membrane of cancer cells, promoting EMT during breast cancer cell invasion, interestingly, by controlling the release of the active TGFβ ligand [ 30 ]. In prostate cancer cells, ECM-deposited latent TGFβ can be activated by membrane type I-matrix metalloprotease (MT1-MMP/MMP14), which then induces the secretion of Wnt5a; the sequential action of TGFβ and Wnt5a sustain EMT and invasiveness of the tumor cells [ 31 ]. Not only glycoproteins, but also glycosaminoglycans, such as hyaluronan, can be induced by TGFβ signaling ( Figure 2 ).…”
Section: Regulation Of Emt By Tgf-βmentioning
confidence: 99%
“…Similar to the point we will discuss later about the reciprocal roles of TGFβ and other cytokines, ECM components such as fibronectin and MMPs are not only induced by TGFβ signaling in mammary epithelial cells, but can themselves provide critical signals that promote the EMT, including control of the activation of TGFβ ligand in the extracellular environment [ 23 ]. The membrane type I-matrix metalloprotease (MT1-MMP or MMP14) promotes EMT and invasiveness by activating extracellular TGFβ, which then induces the secretion of Wnt5a and thus provides a paracrine signal to epithelial prostate cancer cells [ 24 ]. A similar action can be observed for the extracellular glycosaminoglycan hyaluronan, whose synthesis can be induced by TGFβ signaling; hyaluronan activates TGFβ signaling and its downstream transcriptional mediators Snail1 and Twist1, thus promoting EMT and the enrichment of tumor cells in cancer stem cell populations [ 25 ].…”
Section: The Cellular Basis Of Emtmentioning
confidence: 99%